A bibliometric study on clinical research in neonatal encephalopathy - Tan, Shujun; Alimujiang, Gulizuohere; Rejiafu, Nuerya (Frontiers in Pediatrics, 2024)
This research presents a comprehensive review of studies on neonatal encephalopathy conducted between 2005 and 2024, utilizing knowledge graph analysis through CiteSpace and VOSviewer software. A search of the Web of Science core database identified 893 articles, with the United States emerging as a prominent contributor in terms of publication volume. Key co-occurrence keywords identified include 'Hypoxic-ischemic encephalopathy', 'Neonatal encephalopathy', and 'Therapeutic hypothermia'. Notable contributors, such as Seetha Shankaran and Floris Groenendaal, have significantly advanced research in this area. Leading institutions in this field include the University of Washington, while the journal Pediatrics is recognized as a leading publication in the domain of neonatal encephalopathy. These findings provide a solid foundation for guiding future research endeavors.